1995
DOI: 10.1083/jcb.131.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Differential targeting of protein kinase C and CaM kinase II signalings to vimentin.

Abstract: Abstract. Hydrolysis of inositol phospholipids by receptor stimulation activates two separate signaling pathways, one leading to the activation of protein kinase C (C kinase) via formation of diacylglycerol. The other is the inositol trisphosphate (IP3)/Ca 2÷ pathway and a major downstream kinase which is activated is Ca2÷/calmodulin-dependent protein kinase II (CaM kinase II). To examine signaling pathways of C kinase and CaM kinase II to the cytoskeletal protein vimentin, we prepared monoclonal antibodies YT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 75 publications
(105 reference statements)
4
65
0
Order By: Relevance
“…Immunocytochemical studies using TM38 and TM71 revealed that these two sites were phosphorylated at the cleavage furrow during cytokinesis in U251 human glioma cells (Figure 1c and d). Together with previous immunocytochemical studies (Matsuoka et al, 1992;Tsujimura et al, 1994;Ogawara et al, 1995;Takai et al, 1996;Sekimata et al, 1996;Inagaki et al, 1997b) (Table 1).…”
supporting
confidence: 79%
“…Immunocytochemical studies using TM38 and TM71 revealed that these two sites were phosphorylated at the cleavage furrow during cytokinesis in U251 human glioma cells (Figure 1c and d). Together with previous immunocytochemical studies (Matsuoka et al, 1992;Tsujimura et al, 1994;Ogawara et al, 1995;Takai et al, 1996;Sekimata et al, 1996;Inagaki et al, 1997b) (Table 1).…”
supporting
confidence: 79%
“…These data argue that either a properly organized vimentin ®lament network or the vimentin tail domain itself is necessary to retain tsp53 on the cytoskeleton. While the function of the head domain of vimentin has well been described, that of the tail domain is still not completely understood (Ciesielski-Treska et al, 1991;Inagaki et al, 1990;Ogawara et al, 1995;Traub and Vorgias, 1983). Probably, the tail controls the lateral association of IF-protein tetramers and thereby stabilizes the ®lament structure, which may be essential to establish a proper ®lament network (Heins and Aebi, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These phosphorylation events are triggered by a wide range of protein kinases, such as PKA and PKC [15,19], PKG [20], Rho-kinase and Aurora B [21], PAK [22,23], MAPKAP K-2 [10], Cdc2 kinase [24] and CaMKII [25] and involve a large number of serine residues (e.g. Ser 4,[6][7][8][9]25,33,38,41,50,55,65,71,72,82) with a complex pattern of overlapping specificities [15,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, treatment with protein phosphatase inhibitors, such as calyculin-A [15] or okadaic acid [16], results in a dose-and time-dependent increase in vimentin phosphorylation, causing rapid disassembly of pre-existing filaments, delay of fiber assembly and increased levels of soluble vimentin tetramers [15,17,18]. These phosphorylation events are triggered by a wide range of protein kinases, such as PKA and PKC [15,19] [25] and involve a large number of serine residues (e.g. Ser 4,[6][7][8][9]25,33,38,41, 50, 55, 65, 71, 72, 82) with a complex pattern of overlapping specificities [15,26,27].…”
mentioning
confidence: 97%
See 1 more Smart Citation